IMPLEMENTASI KEBIJAKAN PEMBANGUNAN JALAN DINAS PEKERJAAN UMUM DAN PENATAAN RUANG KOTA PONTIANAK - Er Salsabila (Fakultan Ilmu Sosial dan Ilmu Politik Universitas Tanjungpura, 2022)
In the implementation of road construction, problems and obstacles may arise, as happened in the construction of Jalan Dr. Sudarso. The purpose of writing this thesis is to describe the obstacles that occur in the construction process of Jalan Dr. Sudarso as well as analyzing the factors that influence the implementation of the Dr. Road construction policy. Sudarso by the Pontianak City PUPR Service. The problems that occur in road construction Dr. Sudarso, namely the existence of a conflict of interest with traders and parking attendants who set up trading stalls and parking lots on the road to be built. This study uses a qualitative method with analysis of policy implementation using Edward III's theory, namely four variables that affect the success of policy implementation, namely communication, resources, disposition, and bureaucratic structure. (1) Communication; Communication is carried out by direct socialization, holding negotiations, as well as a written communication sent by the City Regional Secretariat to the parking coordinator regarding the arrangement of the Dr. Street network. Sudarso. Communication between the PUPR Service and the community went well so that each party was willing to discuss and listen to each other regarding land acquisition. (2) Resources; Experienced human resources have the skills and abilities to solve problems in order to implement policies. The availability of funds and physical facilities in the form of heavy equipment is also adequate so that it is very supportive of the success of road construction. (3) Disposition; The attitude of the implementor is considered wise in acquiring land, with reference to the social aspect. This raises sympathy for the surrounding community so that the community fully supports the construction of Jalan Dr. Sudarso. (4) Bureaucratic structure; based on SOP to make policy implementation run optimally. There are also various agencies involved that coordinate to support the successful construction of Jalan Dr. Sudarso. The four variables synergize to create success as well as smoothness in the implementation of the construction of Jalan Dr. Sudarso. The Pontianak City PUPR Service is expected to always be consistent in observing the social aspects of the community, so that the initial goal of development, namely the welfare of the community, can be achieved.Keywords: Policy Implementation, Road Construction, PUPR Service